Climatology of polar ionospheric density profile in comparison with mid-latitude ionosphere from long-term observations of incoherent scatter radars: A review. (December 2020) - Kim, Eunsol; Jee, Geonhwa; Ji, Eun-Young; Kim, Yong Ha; Lee, Changsup; Kwak, Young-Sil; Shim, Ja-Soon
Abstract: Although the horizontal density structures of the polar ionosphere have been extensively studied mostly using the F-region peak density or total electron content, there are relatively few studies on the vertical density structures. In this review, we present the climatology of the polar ionospheric density not only in the F-region but also in the E-region and topside ionosphere, in comparison with the mid-latitude ionosphere, using long-term incoherent scatter radar (ISR) observations at Millstone Hill, Tromsø, and Svalbard. The ISR data during the period of 1995–2015 are analyzed to study on the variations with local time, season, and solar/geomagnetic activity. The diurnal variations of the F-region density are much smaller in the polar region than in the mid-latitude, particularly in summer. At Svalbard, there is a characteristic double-peak structure in the diurnal variation of the polar ionosphere in winter only for high solar activity. The diurnal variation of hmF2 decreases with increasing latitude and eventually disappears at Svalbard for low solar activity but the hmF2 and its diurnal variations in the polar ionosphere are remarkably enhanced for high solar activity. The distinctive irregularity in the mid-latitude F1-layer nearly disappears in the polar region, especially at Svalbard. The anomalous seasonal variations of the F-region density are less evident in the polar ionosphere especially for low solar activity and for high magnetic activity conditions. The polar E-region density shows characteristic nighttime peaks induced by auroral precipitation but it does not necessarily increase with solar activity. The topside ionospheric density variations are much stronger in the polar region for high solar activity. Finally, it is found that the polar ionospheric density profiles more strongly respond to increasing solar activity as well as the magnetic activity compared with the mid-latitude ionosphere. Highlights: Diurnal variation of the polar ionosphere is largely much smaller than the mid-latitude ionosphere. But hmF2 shows remarkable diurnal variations for high solar activity in the polar region. Seasonal variations of the ionosphere are less evident and only occur during low magnetic activity in the polar region. Auroral contribution to the E-region density is largest in winter for low solar activity. Ionospheric responses to solar and magnetospheric energy inputs are much more complex in the polar region.